Impact of COVID-19 and mitigation plans on essential health services: institutional experience of a hospital in Ethiopia - Firaol Dandena; Berhanetsehay Teklewold; Dagmawi Anteneh (BMC, 2021)
Abstract Background Health systems around the world are being challenged by an on-going COVID-19 pandemic. The COVID-19 pandemic and associated response can have a significant downstream effect on access to routine health care services, and indirectly cause morbidity and mortality from causes other than the disease itself, especially in resource-poor countries such as Ethiopia. This study aimed to explore the impact of the pandemic on these services and measures taken to combat the effect. Methods The study was conducted at St. Paul's hospital millennium medical college (SPHMMC) from December 15, 2020 to January 15, 2021 using a comparative cross-sectional study design. We collected data on the number of clients getting different essential health care services from May to October 2019 (Pre COVID) and the same period in 2020 (during a COVID-19 pandemic) from the patient registry book. The analysis was done with SPSS version 24 software. Result Overall, the essential services of SPHMMC were affected by the COVID-19 pandemic. The most affected service is inpatient admission, which showed a 73.3% (2044 to 682) reduction from the pre-COVID period and the least affected is maternal service, which only decreased by 13% (3671 to 3177). During the 6 months after the COVID-19 pandemic, there was a progressive increment in the number of clients getting essential health services. Conclusion and recommendation The establishment of a triple setup for fighting against COVID-19, which encompasses non-COVID services, an isolation center and a COVID-19 treatment center, played a vital role in preserving essential health services.